1989
DOI: 10.1128/iai.57.6.1668-1674.1989
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of human gamma interferon by Pseudomonas aeruginosa proteases: elastase augments the effects of alkaline protease despite the presence of alpha 2-macroglobulin

Abstract: Pseudomonas aeruginosa alkaline protease (AP) has recently been shown to produce limited proteolysis of human gamma interferon (IFN--y) and thereby destroy the antiviral and macrophage-activating activities of the lymphokine. In the present study we describe some of the characteristics of Pseudomonas elastase (E) with regard to inactivation of human IFN-,y. The inhibitory effect of E on IFN--y bioactivity differed from that of AP in that the direct effects of E were reduced in the presence of human serum. That… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…These results indicate that in vitro cytokine inactivation by Pseudomonas proteases is selective, requires only limited proteolysis, and in certain instances reflects the cooperative effects of both proteases.Pseudomonas aeruginosa is an important pulmonary pathogen in conditions like cystic fibrosis (15,42). It has been suggested that the ability of P. aeruginosa to establish itself in the respiratory tract may be promoted by its suppressive effects on pulmonary immune responses (2,16,40). The mechanisms of this immunosuppression are not entirely understood, but proteolytic enzymes secreted by the bacterium have been shown to degrade surface receptors on hematogenous cells (36, 43) and inactivate interleukin-2 (IL-2) and gamma interferon (IFN--y) (16,17,41).In the case of human IFN--y, cytokine inactivation was caused by either Pseudomonas alkaline protease (AP) (17) or elastase (E) (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that in vitro cytokine inactivation by Pseudomonas proteases is selective, requires only limited proteolysis, and in certain instances reflects the cooperative effects of both proteases.Pseudomonas aeruginosa is an important pulmonary pathogen in conditions like cystic fibrosis (15,42). It has been suggested that the ability of P. aeruginosa to establish itself in the respiratory tract may be promoted by its suppressive effects on pulmonary immune responses (2,16,40). The mechanisms of this immunosuppression are not entirely understood, but proteolytic enzymes secreted by the bacterium have been shown to degrade surface receptors on hematogenous cells (36, 43) and inactivate interleukin-2 (IL-2) and gamma interferon (IFN--y) (16,17,41).In the case of human IFN--y, cytokine inactivation was caused by either Pseudomonas alkaline protease (AP) (17) or elastase (E) (16).…”
mentioning
confidence: 99%
“…It has been suggested that the ability of P. aeruginosa to establish itself in the respiratory tract may be promoted by its suppressive effects on pulmonary immune responses (2,16,40). The mechanisms of this immunosuppression are not entirely understood, but proteolytic enzymes secreted by the bacterium have been shown to degrade surface receptors on hematogenous cells (36, 43) and inactivate interleukin-2 (IL-2) and gamma interferon (IFN--y) (16,17,41).In the case of human IFN--y, cytokine inactivation was caused by either Pseudomonas alkaline protease (AP) (17) or elastase (E) (16). Significant reductions in antiviral and immunomodulatory activities were associated with limited proteolysis of IFN--y.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there is no evidence that IFN-g1b is vulnerable to the proteolytic activity of human neutrophil elastase, but it is also possible that Pseduomonas proteases may have reduced IFN-g1b bioactivity, since this organism was present in 87% of patients in this study. 41 Similarly, the adverse events observed in patients receiving 1,000 mg IFN-g1b may have been due to other factors, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it may have been an other enzyme than a plasmin-like serine protease. Pseudomonas alkaline protease and metallo elastase (Catanase & Kress 1984;Kress 1986;Horvat et al 1989;Fick et al 1986) could come into question. Exact knowledge of the nature of the tissue destructive properties of each microbe is a prequisite for the prevention of tissue damage and for optimal treatment.…”
Section: Discussionmentioning
confidence: 99%